E-Learning for Senior Citizens - Hetzner, Sonia; Held, Paul (John Wiley & Sons, Inc., 2013)
Keywords: ELSe - e-learning environment; E-Learning; ELSe didactic approach; ELSe development areas; ELSe pedagogical approach

E-Learning for Senior Citizens - Hetzner, Sonia; Held, Paul (Distance and e-learning in transition. Learning innovation, technology and social challenges, 2009)

ICT enhanced learning for older adults: Influencing factors on satisfaction and the role of learning motivation - Lipphardt, Anne-Marie; Held, Paul; Leen-Thomele, Eline; Hain, Lukas (Gerontechnology, 2018)
PURPOSE. Since Lifelong Learning has become a guiding principle of educational policy in many countries across the globe, several concepts in the field of educational gerontology were developed and implemented. In this context, also learning opportunities through ICT were tested and studies have proven a high suitability of e-learning for older people and their potentials for digital inclusion (1, 2, 3). Yet, little research has been done about the influence of learning motivation, personality traits and demographical aspects on e-learning success. METHOD. This paper discusses the results of the implementation and evaluation of four e-learning programs on ICT, culture, mentoring and well-being for older adults with 128 people (94 females, 34 males; mean age 67,12 years, SD 10,485) from five European countries. As part of the evaluation, satisfaction with course preparation and support, information on learning motivation, and aspects of e-learning as method were queried and analyzed with focus on differences with regards to gender, age, nationality, educational level, experience with ICT, life satisfaction, and health status. Learning motivation was further divided into motives of belonging, personal growth, instrumentality, and competition (4). RESULTS AND DISCUSSION. Findings show that older adults across all distinguishing criteria cope very well with diverse aspects of e-learning and highly benefit from the given advantages. No significant differences were found when comparing the subgroups. These results confirm study findings done at national level on suitability of e-learning (5). Differences could be found in learning motivation with regards to age, nationality, health status, gender. Younger participants take part more often for motives of competition, instrumentality and social belonging and older participants for motives of personal growth. Cross-country comparisons show significant differences with regards to diverse aspects in learning motivation. While personal growth was most important for German and Spanish participants, for participants from Finland motives of competition meant the most. As regards gender, men were more likely to take part for reasons of social belonging and instrumentality than women. Overall, results trigger considerations to develop e-learning programs adaptable to certain sub-groups (e.g. country-specific elements). <
Keywords: ICT; educational gerontology; e-learning: learning motivation

Mobile learning concepts for older adults: Results of a pilot study with tablet computers in France and Germany - Hetzner, Sonia; Hetzner, Sonia; Leen-Thomele, Eline; Held, Paul (Springer Verlag, 2016)
This paper sums up the evaluation results of a tablet computer course for older adults. As part of an European research project, the SenApp project, online course modules were developed to teach older adults the first steps on a tablet computer. After the course, a questionnaire was filled in Germany and France (N = 26). The evaluation focused on differences in satisfaction with support and course contents and in learning routines between age groups, education level, countries and pre-experience conditions. Main findings suggest that both courses were rated good, but that some support and content aspects were rated less good in France and by lower educated participants, by participants with less pre-experience in e-learning and by older age groups. This suggests that future course concepts should be created more flexible with different learning amounts for different experience levels and that especially support possibilities can be improved for some group
Keywords: Older adults; ICT courses; Tablet computer

Mobile Learning Concepts for Older Adults: Results of a Pilot Study with Tablet Computers in France and Germany - Hetzner, Sonia; Leen-Thomele, Eline; Held, Paul (SPRINGER INTERNATIONAL PUBLISHING AG, GEWERBESTRASSE 11, CHAM, CH-6330, SWITZERLAND, 2016)
This paper sums up the evaluation results of a tablet computer course for older adults. As part of an European research project, the SenApp project, online course modules were developed to teach older adults the first steps on a tablet computer. After the course, a questionnaire was filled in Germany and France (N = 26). The evaluation focused on differences in satisfaction with support and course contents and in learning routines between age groups, education level, countries and pre-experience conditions. Main findings suggest that both courses were rated good, but that some support and content aspects were rated less good in France and by lower educated participants, by participants with less pre-experience in e-learning and by older age groups. This suggests that future course concepts should be created more flexible with different learning amounts for different experience levels and that especially support possibilities can be improved for some groups.
Keywords: Older adults; Tablet computer; ICT courses

Mobile Learning for older adults: new learning concepts for seniors without e-skills - Leen-Thomele, Eline; Hetzner, Sonia; Held, Paul (8, 2015)
This qualitative research investigates possibilities for mobile learning for older adults. Three groups of older adults (N = 23) were interviewed: experienced ICT teachers, older adults who use a tablet computer and older adults without experience in using a tablet computer. Questions about motives to use a tablet, attitudes, learning techniques, obstacles and benefits of learning and reasons for non-use were asked in semi-structured interviews. Results confirm previous findings: Although the group of older adults is very heterogenic, some basic principles for learning and motivating older adults can be deviated: possibilities for rehearsing, patience, daily life examples to show the added value and reductions of fears and negative attitudes are very important. To motivate older adult to use tablets, it is key to show possibilities and support them with suitable learning material, online or face-to-face. In general, users of tablets are very content and rate tablets as easy to use also with limited technical knowledge. Therefore, tablets are a promising device for older adults who are not willing or daring to use ICT yet. This knowledge is the starting point for the project SenApp, an online course for older adults about the first steps of tablet use.
Keywords: tablets; mobile learning; older adults; life-long learning

NEW CONCEPT FOR DIGITAL INCLUSION—ONLINE AND MOBILE LEARNING PROGRAMS FOR OLDER PERSONS - Lipphardt, Anne-Marie; Leen-Thomele, Eline; Coroian, Anamaria Elena; Held, Paul (Innovation in Aging, 2017)
This paper sums up the evaluation results of two e-learning ICT courses for older adults: a tablet computer course and a regular computer course, and discusses the advantages of mobile learning and e-learning for older adults. As part of an European research project, the SenApp project, online course modules were developed, to teach older adults the first steps on a tablet computer, and evaluated (N=37, age range 58–93). The other course we analyzed, was an online learning course with regular computers and part of the LernHaus project in Germany (N=29, age range 50–89). The evaluation focused on differences in satisfaction with support and course contents and in learning routines between age groups, education level, countries and pre-experience conditions. Main findings suggest that all courses were rated good, compliance was very good and that support was a key factor for course success. Mobile learning was slightly easier for new learner

Older Adults and Learning Technology: Innovations in Adults‘ and Seniors‘ Education - Lipphardt, Anne-Marie; Leen-Thomele, Eline; Held, Paul; Coroian, Anamaria Elena (Innovation in Aging, 2017)
This paper discusses the results of an empirical survey with 187 peopleabove the age of 50 years (mean age 68,4 yrs) on their digital behaviors, motivation as well as interests, and barriersagainst the use of new technologies and presents innovative learning approaches for older adults. The interviewswere conducted in five European countries (Finland, France, Germany, Ireland, Spain) as part of the research projectEHLSSA. The findings show that more than half of older adults are computer users and have Internet access at home.Reasons why they deal with digital technologies are mainly because they want to participate in the information societyand keep pace with the younger generation. Main obstacles are physical challenges, fears and reservations totechnology and the Internet, insecurity on how to work with digital devices and with regards to possibilities for supportin case something goes wrong or questions arise. According to the interviewees, successful learning concepts focuson experimental and active learning, including a more diverse media use, a series of real life examples, and theconnection with the daily life of older adults. Responses of ICT-beginners and experienced ICT-users were analyzedseparately and compared. The results have been used as the basis for the adaptation of learning approaches for thirdlevel education and the development of online course modules in the field of digital literacy and humanities-relatedtopics. The implementation of these courses started in May 2016 and will be completed in June 2017 with at least 800 participant

weSPOT: A Personal and Social Approach to Inquiry-Based Learning - Mikroyannidis, Alexandros; Okada, Alexandra; Scott, Peter; Rusman, Elen; Specht, Marcus; Stefanov, Krasenn; Protopsaltis, Aristidis; Held, Paul; Hetzner, Sonia; Kikis-Papadakis, Kathy; Chaimala, Foteini (Journal of Universal Computer Science, 2013)
Keywords: Inquiry-based learning; scientific inquiry; personal learning environment; cloud learning environment